The Effects of Attitudinal and Demographic Factors on Intention to Buy Pirated CDs: The Case of Chinese Consumers - Kwong, Kenneth K. (Journal of business ethics, 2003)
This study examines the impact of attitude toward piracy on intention to buy pirated CDs using Chinese samples. Attitude toward piracy is measured by a multi-item scale that has been shown to have a consistent factor structure with four distinct components, namely, social cost of piracy, anti-big business attitude, social benefit of dissemination, and ethical belief. Our findings reveal that social benefit of dissemination and anti-big business attitude have a positive relationship with intention to buy pirated CDs while social cost of piracy and ethical belief have a negative relationship. Among these components, ethical belief tends to most strongly predict intention to buy pirated CDs. Demographic variables such as gender and age also help explain the respondents' intention to buy pirated CDs. In addition, those respondents with experience of buying pirated CDs would tend to be more likely to buy pirated CDs than those without such experience. The results are discussed with a view to helping copyright businesses to effectively suppress piracy, and directions for future research are suggested.